An Efficient Electroporation Protocol for the Genetic Modification of Mammalian Cells - Chicaybam, Leonardo; Barcelos, Camila; Peixoto, Barbara; Carneiro, Mayra; Limia, Cintia Gomez; Redondo, Patrícia; Lira, Carla; Paraguassú-Braga, Flávio; Vasconcelos, Zilton Farias Meira De; Barros, Luciana; Bonamino, Martin Hernán (Frontiers in Bioengineering and Biotechnology, 2017)
Genetic modification of cell lines and primary cells is an expensive and cumbersome approach, often involving the use of viral vectors. Electroporation using square wave generating devices, like Lonza´s Nucleofector, is a widely used option, but the costs associated with the acquisition of electroporation kits and the transient transgene expression might hamper the utility of this methodology. In the present work we show that our in house developed buffers, termed Chicabuffers, can be efficiently used to electroporate cell lines and primary cells from murine and human origin. Using the Nucleofector II device, we electroporated 14 different cell lines and also primary cells, like mesenchymal stem cells and cord blood CD34+, providing optimized protocols for each of them. Moreover, when combined with Sleeping Beauty based transposon system, long-term transgene expression could be achieved in all types of cells tested. Transgene expression was stable and did not interfere with CD34+ differentiation to committed progenitors. We also show that these buffers can be used in CRISPR-mediated editing of PDCD1 gene locus in 293T and human peripheral blood mononuclear cells. The optimized protocols reported in this study provide a suitable and cost-effective platform for the genetic modification of cells, facilitating the widespread adoption of this technology.